The allegiance of Thomas Hobbes - Collins, Jeffrey R. (Oxford University Press, 2005)
The Allegiance of Thomas Hobbes offers a new interpretation of Thomas Hobbes's response to the English Revolution. By focusing on his religious thought, it debunks the standard view of him as a royalist, and recovers his sympathies with the religious projects of the 1640s and 1650s. This reinterpretation culminates with an exploration of Hobbes's surprising sympathies with Oliver Cromwell and his supporters. By placing Thomas Hobbes within fresh contexts, Professor Collinsoffers a new angle of vision on the religious significance of the English Revolution itself. - ;The Allegiance of Thomas Ho.